Counter-hegemonic Resistance in China's Hong Kong: Visualizing Protest in the City - Garrett, Daniel Paul (Springer, 2015)
This book and associated collection of visual data and sociological observations examine how the Hong Kong Special Administrative Region (SAR) has been visually re-imagined, transformed, and utilized by its subalterns in the post-Handover period to reproduce their aspirations and demands for greater democracy and social justice while simultaneously contesting the hegemonic pressure exerted by China under the “One Country, Two Systems” ideology. It provides a rich visual description and narrative of how Hong Kong’s many repressed social and political actors have struggled to make their voices heard under its competitive authoritarian political system. The book addresses the growing scholarly interest in the visual analysis of global protests and social movements as salient sources of sociological data and on the creation of meaning. By innovatively tackling the visual culture and visuality of subaltern resistance in Hong Kong it contributes to our understanding of contentious SAR-China politics and the New Social Movement, and will be of great interest to Hong Kong, resistance, social movement, and visual studies scholars.